Space Time Block Codes With Spatial Modulation (International Journal of Engineering and Computer Science, 2015)
A new multiple-input multiple-output (MIMO) transmission scheme is proposed and it is called space-time block coded spatial modulation (STBC-SM. This scheme is a combination of both Space Time Block Codes and Spatial modulation. By combining we can avoid the drawbacks of the both systems and make use of the advantages of the system.The transmit information symbols are expanded both in space and time domains and also to the spatial (antenna) domain which corresponds to the on/off status of the transmit antennas available at the space domain.A general technique is presented for the design of the STBC-SM scheme for any number of transmit antennas. Besides the high spectral efficiency advantage provided by the antenna domain, the proposed scheme is also optimized by deriving its diversity and coding gains to exploit the diversity advantage of STBC. A low-complexity maximum likelihood (ML) decoder is given for the new scheme which profits from the orthogonality of the core STBC. The performance advantages of the STBC-SM over simple SM and over V-BLAST are shown by simulation results for various spectral efficiencies and are supported by the derivation of a closed form expression for the union bound on the bit error probability.